The Role of Artificial Intelligence in Developing Digital Skills - Pintea, Florentina; Iordan, Victoria; Purda, Daniel (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
The rapid evolution of Artificial Intelligence (AI) is transforming the landscape of digital education and reshaping the competencies required in the modern technological ecosystem. This paper explores the role of AI in developing digital skills, emphasizing how intelligent tools, adaptive learning platforms, and automated assessment systems facilitate personalized learning pathways and enhance students’ ability to acquire and refine technical competencies. By integrating AI-driven solutions into the learning process, educators can better address individual learning needs, support problem-solving and critical thinking, and create dynamic and interactive educational environments. The study also highlights the challenges associated with adopting AI in education, including ethical considerations, digital literacy gaps, and the need for continuous teacher training. Overall, the paper argues that AI serves as a catalyst for developing essential digital skills, preparing students for the demands of future professions and contributing to a more efficient and inclusive educational system.